Menanamkan Nilai Disiplin Anak pada Lingkungan Keluarga di Desa Sungai Pinang Lama Kecamatan Sungai Tabuk Kabupaten Banjar - Maryana, Maryana (Jurnal Pendidikan Kewarganegaraan, 2015)
Inculcate discipline for children is certainly not easy , requiring a habituation and perseverance , and certainly it needs the example of their parents . In other words , all of things must start from the parents . As caregivers and mentors in the family , the parents are the foundations for their children s behavior. Attitudes, behaviors and habits of the elderly has always been viewed, assessed and imitated by children that consciously or unconsciously become habits for them anyway. Whatever the reason why parent gives discipline for the child is for their future. Hopefully that one day in the future the child will have Â good morals according to expectations of parents.Keywords : discipline , family environments.